Pengaruh konsentrasi auksin terhadap pertumbuhan setek pucuk tanaman ciplukan(Physalis peruviana L.) - Rizal Nursachya; Endeh Masnenah; Iis Aisyah (Composite : Jurnal Ilmu Pertanian, 2023)
Ciplukan (Physalis peruviana L.) has potential as a medicinal plant. The availability of quality Ciplukan seeds for farmers were still low, while there were also very little information on ciplukan propagation techniques. Therefore it were necessary to study ciplukan propagation techniques. The objectives of research were to study the effect of auxin concentration on the growth of Ciplukan shoot cutting. This experiment have been done at the Waaida Farm in Lembang, Pamulihan village, Sumedang, at an altitude of 943 meters above sea level and temperatures of 18-22 oC, from June to August 2021. The experiment used was a Randomized Block Design (RBD), consisted of five treatments namely A (0 ppm); B (100 ppm); C (200 ppm); D (300ppm); and E (400 ppm) and replicated three times. The result was indicated that the concentration of auxin had an effect on the height of cutting (28 DAP and 42 DAP) and the number of leaves (28 DAP, 42 DAP and 56 DAP) but had no effect on the root volume, fresh weight and dry weight of cutting of Ciplukan. Auxin concentration of 100 ppm (B) had a better effect on the height of cutting (28 DAP and 42 DAP) and number of leaves (28 DAP, 42 DAP and 56 DAP).